2020
DOI: 10.1029/2020gc009176
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Late Holocene Dead Sea Sediments as a Monitor of Regional Hydroclimate

Abstract: Microbial sulfate reduction (MSR) occurs commonly in reducing redox environment (Canfield & Berner, 1987; Morse & Cornwell, 1987; Wilkin & Barnes, 1997) where it can affect significantly the magnetic properties of sediments by causing titanomagnetite dissolution and by triggering authigenic greigite (Fe 3 S 4) precipitation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…Thermal demagnetization curves from Ein‐Feshkha and Ein‐Gedi (Figure 4f2 and 4i2 respectively) are in agreement with the conclusions of Ebert et al. (2020), showing low blocking temperature of ∼350°C for the greigite‐bearing sediments of Ein‐Feshkha and higher blocking temperature range, from ∼350°C to 550°C, for the titanomagnetite‐bearing sediments in Ein‐Gedi. Acquisition of a gyroremanent magnetization (GRM) during AF demagnetization (e.g., Sagnotti & Winkler, 1999; Snowball, 1997) was observed only in few samples (Figures 4b, 4e, and 4h).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Thermal demagnetization curves from Ein‐Feshkha and Ein‐Gedi (Figure 4f2 and 4i2 respectively) are in agreement with the conclusions of Ebert et al. (2020), showing low blocking temperature of ∼350°C for the greigite‐bearing sediments of Ein‐Feshkha and higher blocking temperature range, from ∼350°C to 550°C, for the titanomagnetite‐bearing sediments in Ein‐Gedi. Acquisition of a gyroremanent magnetization (GRM) during AF demagnetization (e.g., Sagnotti & Winkler, 1999; Snowball, 1997) was observed only in few samples (Figures 4b, 4e, and 4h).…”
Section: Resultssupporting
confidence: 89%
“…Ebert et al. (2020) suggested that the high values of magnetic parameters at Og and Ein‐Feshkha sections (170–320 cm) correspond to high content of the mineral greigite; intermediate values of magnetic parameters, at Ein‐Gedi section (0–120 and 200–260 cm) and at Ein‐Feshkha section (0–170 and 320–460 cm), indicate lower content of greigite; and low magnetic parameters values at Ein‐Gedi section (130–200 cm) are associated with dominance of the mineral titanomagnetite. The ratios and the MDF shown in Figure 3 are in agreement with these conclusions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations